Escola municipal: a rede de ensino da Capital Paulista em revista (1968-1985) - Romero, Rosana Aparecida Silva (2016)
In this research a magazine called Escola Municipal, which was published by Prefeitura Municipal de São Paulo from 1968 until 1985, was analyzed. The focus was mainly in Cultural History and its features, learning about continuities and breaks, covering the aspects about the editorial projects. There were some questions which guided our work: which topics the magazine reported? How were they done and to whom? The themes of the articles and the frequency they were posted were taken as an object, allowing its organization into categories and were related to each other, and identifying the production of a memory of public schools and a pedagogical approach to the network. This proposal revealed a conception of a student defined as “culturally deprived and undernourished”. On the one hand, the teachers were considered national heroines who carried on education, and therefore civility to everywhere in town, but on the another hand, were not considered authors of their own work and simply performers of an approach of the members in the Municipal Department of Education. The analysis of the article also revealed an option which was to disclose programs, projects, celebrations and buildings, and it was concluded then that the magazine aimed to produce a memory of the public school, providing the city of São Paulo as the keeper of an efficient educational management to implement the LDB 5692/71. For this reason it was assumed that the values were very close to the ones during military dictatorship, although politics issues were not explicit approached, its footprints were seem in an unclear speech of “Order and Progress”